Assessment of structural and cross-cultural validity of the Disabilities of the Arm, Shoulder and Hand questionnaire: a scoping review. (March 2023) - de Klerk, Susan
Introduction: The Disabilities of the Arm, Shoulder and Hand (DASH) Questionnaire is a patient-reported outcome measure (PROM) that has been translated and cross-culturally adapted to at least 50 languages. Since the measure was developed in 1996, many researchers have reported on the construct validity (including structural and cross-cultural validity) of this instrument following translation and cross-cultural adaptation. The aim of this scoping review was to identify the methods used for the psychometric evaluation of structural and cross-cultural validity of the DASH questionnaire. Methods: The updated methodological guidance for the conduct of scoping reviews and the PRISMA Extension for scoping reviews checklist was utilised. EBSCOHost (Academic Search Premier, Africa Wide, CINAHL, E-Journals and Medline), PubMed and Google Scholar were searched for articles (published between 1996–2022) and considered against the eligibility criteria. Results: The scoping review collated evidence across 50 articles (37 language versions) of the evaluation of structural and cross-cultural validity of the DASH questionnaire. Three articles conducted confirmatory factor analysis (CFA) to assess structural validity, and none performed Multiple Group Confirmatory Factor Analysis (MGCFA) to assess cross-cultural validity. Conclusion: The COnsensus-based Standards for the selection of health Measurement Instruments (COSMIN) taxonomy propose that structural validity is best evaluated through CFA, with prior evidence of dimensionality. Additionally, cross-cultural validity (measurement invariance) is to be evaluated through MGCFA. This review identified that CFA is utilised infrequently and that to date cross-cultural validity has not been appropriately assessed for translations of the DASH questionnaire.